Plasma assisted conversion of carbon dioxide in low-pressure gas discharges - Dudin, S.V.; Zykov, A.V.; Yakovin, S.D. (Вопросы атомной науки и техники, 2019)
Experimental results of comparative study of carbon dioxide conversion efficiency to CO and O₂ in the plasmas of different low-pressure discharges are presented. Inductively coupled plasma source, magnetron discharge and anode layer discharge in Hall-type ion source were used in CO₂ pressure range 0.5 … 3 mTorr. It is shown that the best combination of high conversion rate with significant energy efficiency of the conversion is demonstrated by the ICP source. Представлено експериментальні результати порівняльного дослідження ефективності конверсії діоксиду вуглецю в СО і О₂ у плазмі розрядів низького тиску. Джерело індуктивно зв'язаної плазми, магнетронний розряд і розряд з анодним шаром в іонному джерелі холлівського типу використовувалися в діапазоні тисків CO₂ від 0,5 до 3 мТорр. Показано, що оптимальне поєднання високого коефіцієнта конверсії зі значною енергоефективністю демонструє джерело плазми з ВЧ-розрядом індукційного типу. Представлены экспериментальные результаты сравнительного исследования эффективности конверсии диоксида углерода в СО и О₂ в плазме разрядов низкого давления. Индуктивно связанный источник плазмы, магнетронный разряд и разряд с анодным слоем в ионном источнике холловского типа использовались в диапазоне давлений CO₂ от 0,5 до 3 мТорр. Показано, что наилучшее сочетание высокого коэффициента конверсии со значительной энергоэффективностью демонстрирует источник плазмы с ВЧ-разрядом индукционного типа.